An Experiential Learning Activity Based on Developing Critical Thinking Skills on Thai Political System Stories for Matthayom 2 Students in Ratchathewi, Bangkok - Kunthasa, Kanyarat; Punyawuttakul, Wasin (Journal of Buddhist Education and Research (JBER), 2025)
This research aimed to 1) study the current situation and problems of organizing learning activities in the social studies, religion and culture subject group on the topic of important changes in the Thai political system for Matthayom 2 students. 2) To develop experiential learning activities as a base for developing critical thinking skills on the topic of major changes in the Thai political system for Matthayom 2 students in Ratchathewi District, Bangkok. This research is qualitative research. The research method and data collection were conducted through interviews with social studies teachers and experimental group of Matthayom 2 students in Ratchathewi District, Bangkok. The data were analyzed through classification of study issues as specified. Data reliability was checked by triangulating the data. The research instruments consisted of 1) semi-structured interview forms. 2) Experiential learning activities to develop critical thinking skills on important events of the Thai political system for Matthayom 2 students. The research results found that 1) the current situation and problems in organizing learning activities: there is quite a lot of learning content. Teaching involves memorization and lectures, which causes learners to not cooperate in learning and lack analytical thinking that is linked to logic. 2) Organizing learning activities using experience as a base to develop critical thinking skills on important events of the Thai political system for Matthayom 2 students. This results in students developing critical thinking skills, knowing how to analyze and synthesize more, and seeing their own abilities more.